(untitled) (Research, Society and Development, 2024)
Introduction: Persistent pulmonary hypertension of the newborn is a neonatal respiratory and vascular pathology with a high mortality rate. Furthermore, its prevalence is 1 to 2 per 1000 live births, accounting for 8%-10% of neonatal deaths. The therapeutic approach involves supporting pulmonary recruitment and pharmacological vasodilation, most notably sildenafil. Methodology: The study is a narrative review of the literature that was carried out from the PUBMED database using the keywords “Persistent Pulmonary Hypertension of the Newborn” and “Sildenafil”, with the time filter in the last 30 years (1994- 2023). Discussion: Physiologically, during fetal life, the lungs remain filled with fluids, but immediately after birth, pulmonary vascular resistance decreases drastically, allowing alveolar oxygen tension and ventilation to be possible. However, in the pathogenesis of neonatal persistent pulmonary hypertension, there is an increase in pulmonary vascular resistance and remodeling of the vascular structure after birth, which potentiate this exaggerated vasoconstriction. Therefore, the standard exam for investigating the pathology is echocardiography. Sildenafil is a drug used to treat neonatal persistent pulmonary hypertension, as it enhances better blood flow and better delivery of oxygen to tissues, through its physiopharmacology aimed at vasodilation secondary to inhibition of phosphodiesterase-5. Conclusion: Neonatal persistent pulmonary hypertension is still one of the main neonatal pathologies with high morbidity and mortality in the neonatal population, due to the complexity of presentations and the variation in therapeutic responses to pharmacotherapy.